Chinese returnees' conceptions of positive career outcomes after graduating from Australian universities – quantitative findings. (July 2015) - Lin-Stephens, Serene; Uesi, John; Doherty, Julie
This paper reports the quantitative findings of a study on conceptions of positive career outcomes held by Chinese students who returned home to work after gaining higher education qualifications in Australia. The study explores what positive career outcomes mean to Chinese returnees, the actual positive career outcomes Chinese returnees have experienced and contributing factors to the positive career outcomes achieved. Both quantitative and qualitative research methods are used and here the analysis of the quantitative findings is presented. The survey data show that Chinese returnees assign greater importance to 'soft outcomes' relating to personal and life fulfilment than 'hard outcomes' such as employment results. Also, the discrepancy between the returnees' ideal and actual outcomes is greater in the soft outcomes than the hard outcomes. Statistical analysis indicates three emergent, distinct groups of conceptions of positive career outcomes. The qualitative findings will be presented separately.